Pengaruh Penggunaan Smartphone Terhadap Interaksi Sosial anak pada TK Al-Karomah Kabupaten Lebong - Hartati, Meri; Taufik, Ahmad; Santika, Hera; Andani, Lesi (Zuriah : Jurnal Pendidikan Anak Usia Dini, 2021)
Smartphones are sophisticated tools that have a variety of interesting features and provide various applications. Thus, the use of smartphones is increasing in number of enthusiasts every year. The use of smartphones in early childhood can have a positive impact if used more wisely and under strict supervision from parents, but can also produce negative impacts outside the strict supervision of their parents. the goal of parents giving smartphones to early childhood children as an online learning media tool and also to add insight that has educational value. This study aims to determine the level of influence of smartphone use on social interaction in Al-Karomah Kindergarten, Lebong Regency, aged 5 to 7 years. As for the research method used, namely quantitative research methods using analytical surveys by case control. While the population is the guardians of Al-Karomah Kindergarten students, Lebong Regency. Data collection techniques in this study used questionnaires and interviews. The results showed that the data on the influence of smartphone use on social interaction in Al-Karomah Kindergarten reached 91 percent for the case category that frequently used smartphones and 9% for the category of rarely using smartphones. Based on the results of the analysis which states that the influence of smartphone use on social interactions reaches 85% for the frequent category and 80% for the infrequent category of smartphone use, this shows a positive influence on social interaction.